5-4x=x-35-4x+4x=x-3+4x (adding 4x on both side)5=5x-35+3=5x-3+3 (adding 3 on both side)8=5xx=8/5
x-4x=5 (1)x-(4)x=5 (-3)x=5 x= 5/(-3) x= -5/3
If the questions asks: (3)/(4x+2) = (5)/(4x-6) then x = -(7/4)
You have 2 equations and 2 unknowns so you can solve 2x-3y = -11 y = 4x -3 2x - 3y = -11 -4x + y = -3 multiply 1st equation by 2 both sides: 4x-6y = -22 -4x + y = -3 add: -5y = -25 y = 5 substitute y = 5 into either equation: -4x+y = -3 -4x +5 = -3 -4x = -8 x = 2
16x2 - 25 = (4x + 5) ( 4x - 5)
4x - 3 = 5 4x = 5 + 3 4x = 8 x = 8/4 x = 2
5+4x-7 = 4x+3-x 4x-2 = 3x+3 4x-3x = 3+2 x = 5
5-4x=x-35-4x+4x=x-3+4x (adding 4x on both side)5=5x-35+3=5x-3+3 (adding 3 on both side)8=5xx=8/5
4x-5=7 4x=12 x=3
7x-5+2x=3-4x+12 7x+2x-5=3+12-4x 9x-5=15-4x 9x+4x-5=15-4x+4x 13x-5=15 13x-5+5=15+5 13x=20 13x/13=20/13 x=20/13
If that's - 4x, the answer is (2x + 3)(2x - 5) If that's + 4x, the answer is (2x - 3)(2x + 5)
The equation 4x + 5 = 2 has the solution 4x = -3 and x = - 3/4 (minus 3/4).
4x - 3 = 17 4x = 17 + 3 4x = 20 x = 20 / 4 x = 5
4x + 5 < 5x + 3 5 < x + 3 x > 2
x-4x=5 (1)x-(4)x=5 (-3)x=5 x= 5/(-3) x= -5/3
5+4x-7=4x+3-1x 4x-2=3x+3 (combined the like terms) +2 +2 (add 2 to both sides) 4x=3x+5 -3x -3x (subtract 3x from both sides) x+5
5 + 4x - 7 = 4x + 3 - x (eliminate alike terms in both sides)5 - 7 = 3 - x (leave the variable alone by itself)5 - 7 - 3 = 3 - 3 - x-5 = -x (multiply both sides by -1)5 = x